2016
DOI: 10.1128/genomea.00245-16
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome Sequence of the Dutch Veterinary Coxiella burnetii Strain NL3262, Originating from the Largest Global Q Fever Outbreak, and Draft Genome Sequence of Its Epidemiologically Linked Chronic Human Isolate NLhu3345937

Abstract: The largest global Q fever outbreak occurred in The Netherlands during 2007 to 2010. Goats and sheep were identified as the major sources of disease. Here, we report the first complete genome sequence of Coxiella burnetii goat outbreak strain NL3262 and that of an epidemiologically linked chronic human strain, both having the outbreak-related CbNL01 multilocus variable-number tandem-repeat analysis (MLVA) genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The CbNL01 genotype was identified mostly in strains isolated from goats and specifically from human patients, indicating that goats harboring the CbNL01 genotype strain were most likely the source of the large human Q fever outbreak in The Netherlands. These genotyping studies confirmed the earlier observed epidemiological link between an increase in human Q fever cases and a high abortion rate in goats (Enserink, 2010 ; van der Hoek et al, 2010 ; Roest et al, 2011a , b ; Kampschreur et al, 2013 ; Kuley et al, 2016 ). Additionally, the genotyping studies also showed that the CbNL12 genotype was majorly associated with strains originating from cattle and rarely with strains from goat, sheep and humans (Roest et al, 2011a , b ; Tilburg et al, 2012c ; Mori et al, 2013 ).…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…The CbNL01 genotype was identified mostly in strains isolated from goats and specifically from human patients, indicating that goats harboring the CbNL01 genotype strain were most likely the source of the large human Q fever outbreak in The Netherlands. These genotyping studies confirmed the earlier observed epidemiological link between an increase in human Q fever cases and a high abortion rate in goats (Enserink, 2010 ; van der Hoek et al, 2010 ; Roest et al, 2011a , b ; Kampschreur et al, 2013 ; Kuley et al, 2016 ). Additionally, the genotyping studies also showed that the CbNL12 genotype was majorly associated with strains originating from cattle and rarely with strains from goat, sheep and humans (Roest et al, 2011a , b ; Tilburg et al, 2012c ; Mori et al, 2013 ).…”
Section: Introductionsupporting
confidence: 86%
“…In the present study we report the new genome sequences of 11 C. burnetii strains. The reconstruction of the genome sequences of the NL3262 and NLhu3345937 strains was described before (Kuley et al, 2016 ). Table 1 is a summary of the main features of the sequenced genomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations